Management Strategies and Environmental Accounting in Economic Entities. A Contribution to Sustainable Development - Ionescu, Cicilia; Chivu, Ramona; Chivu, Marin (Journal of Economic Development, Environment and People, 2014)
Abstract: The economic transactions made in an causes interactions with the environment, in some cases occurring adverse environmental effects. Progressive degradation of the natural environment and increasing social concern before this event, converted protect the environment in one of the most important strategic actions amendment requiring entities to include consideration of environmental issues. The general objective of this study is to analyze business practices related to environmental issues, both in its accounting treatment and environmental management strategies to entities that perform activities of environmental degradation.